Lumbosacral Degenerative Stenosis in the Dog - Janssens, L. A. A.; Moens, Y.; Coppens, P.; Peremans, Kathelijne; Vinck, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A total of thirtyfive dogs with a Hansen type two disc protrusion of the lumbosacral region were operated upon with a technique consisting of dorsal decompression, dorsal anulectomy and disc curettage. The presurgical signs existed for 14 months (mean) and 97% of the animals had been treated unsuccessfully with antiinflammatory drugs. The mean age at the time of surgery was 7,2 years and the mean weight 28 kg. Seventyone percent of the animals were males. A postsurgical questionnaire was mailed to the owners – mean 30 months – after surgery. The results of the surgery were such that 69% of the owners reported that their dog ameliorated after surgery of which 53% found their dog to be completely cured. Comparing the surgical results of this group with a comparable group of animals operated with a dorsal decompression technique alone (without anulectomy), and of which the owners were questioned with the same questionnaire, yielded identical clinical results. Our conclusion therefore is, that the more aggressive and invasive surgery which is neither suitable nor appropriate in that subgroup of patients with lumbosacral degenerative stenosis, plus a type II Hansen disc protrusion and without any, neurological deficit.The results of the surgical treatment of Hansen type II disc protrusion are described. Owners reported that 69% of the patients improved following the operation and that 53% were cured.
Keywords: Canine lumbo-sacram; decompression